Kisspeptin-10: A Predictor for Fetal Growth Restriction among Preeclamptic Women that Discriminated Early Onset Cases - Manal Madany Abdalqader; Shatha Sami Hussein; Huda Fadhil Jadi; Wassan Nori (Clinical and Experimental Obstetrics & Gynecology, 2024)
Background: Preeclampsia (PE) is a major cause of maternal and neonatal morbidity. Fetal growth restriction (FGR) shares many pathophysiological roles with PE. Kisspeptin-10 is a peptide secreted by placental syncytium. It was linked to many adverse pregnancy events. The current study aimed to examine Kisspeptin’s-10 role in predicting FGR in PE pregnancies and to verify whether it can predict its onset as early or late FGR. Methods: An observational case-control study enrolled 120 eligible cases at matched gestational age (28–40 weeks) and body mass index (BMI); they were divided into 2-groups: (60) healthy controls and (60) PE cases. PE cases were subdivided into early onset FGR (28/60), who had a gestational age less than 34 weeks, and late-onset FGR (32/60) with a gestational age equal to 34 weeks. A collection was made of the following data: first: pregnant primary criteria [age, BMI, systolic and diastolic blood pressure (BP), and urine for albumin], second: serum Kisspetein-10 was evaluated via enzyme-linked immunosorbent assay (ELISA), and third: ultrasonic criteria [estimated fetal weight, resistance, and pulsatility index (RI, PI)] were recorded for all. Results: Serum Kisspeptin-10 was significantly higher among the controls (309.56 ± 67.72) followed by late-onset FGR and early onset FGR (235.46 ± 68.97) vs. (212.09 ± 58.44) ng/dL; p = 0.0001 respectively. It was negatively linked to systolic, diastolic BP, and urine for albumin; Pearson correlation coefficient (r) was (–0.29, –0.48, –0.28) respectively; p < 0.0001, 0.0018, 0.028 respectively. Kisspeptin-10 was positively linked to estimated fetal weight (r = 0.27; p = 0.034); it had an odds ratio (OR) of 3.04; 95% confidence interval of (1.37–4.765); p = 0.0001 in discriminating healthy pregnancies from FGR cases. Conclusions: The significant correlation of Kisspeptin-10 with PE parameters and estimated fetal weight with high sensitivity, specificity and reliable area under the curve in predicting early onset FGR cases make it recommended for practice in predicting FGR onset.